2014
DOI: 10.3945/ajcn.113.074724
|View full text |Cite
|
Sign up to set email alerts
|

Similar metabolic responses in pigs and humans to breads with different contents and compositions of dietary fibers: a metabolomics study

Abstract: Our results indicate that pigs are a suitable model for human metabolic studies in food research. The human trial was registered at clinicaltrials.gov as NCT01316354. The animal experiment was conducted according to a license obtained by the Danish Animal Experiments Inspectorate, Ministry of Food, Agriculture and Fisheries, Danish Veterinary and Food Administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 34 publications
0
62
0
1
Order By: Relevance
“…Nielsen et al (58) compared that the metabolomic responses to test meals containing different types of bread were similar in pigs and human subjects and concluded that pigs were a suitable model for human metabolic studies in food research. However, only a few studies have used pigs to assess the impact of WG consumption on cardiovascular health so more work in this area is needed before firm conclusions about their value.…”
Section: Mechanistic Studies On Whole Grainsmentioning
confidence: 99%
“…Nielsen et al (58) compared that the metabolomic responses to test meals containing different types of bread were similar in pigs and human subjects and concluded that pigs were a suitable model for human metabolic studies in food research. However, only a few studies have used pigs to assess the impact of WG consumption on cardiovascular health so more work in this area is needed before firm conclusions about their value.…”
Section: Mechanistic Studies On Whole Grainsmentioning
confidence: 99%
“…Recently, changes in metabolomic profiles due to dietary intervention with different types of bread were evaluated in some studies, providing a list of potential biomarkers of dietary intake (Beckmann et al 2013;Bondia-Pons et al 2013;Bondia-Pons et al 2011;Lankinen et al 2011;Moazzami et al 2012;Nielsen et al 2014). Due to the intervention character of these studies, they were performed on a relatively small number of subjects and under specifically controlled dietary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pigs and human subjects had similar relative metabolic changes for twenty-one out of twenty-six metabolites that were predictive of the different diet interventions in both species, indicating that pig models give a good reflection of human metabolism of cereals. Among the compounds that were different between the refined and whole-grain rye diets for both pigs and human subjects in this study were phosphatidylcholines 38 : 4 and 36 : 4, and lysophosphocholine 18 : 1, which were all elevated on the rye kernel diet compared with the refined wheat bread diet (17) . These initial studies had focused on a high-fibre rye bread diet, based on whole-grain rye and rye bran, compared with a fibre (wheat cellulose) matched refined wheat diet.…”
Section: Metabolomic Insights Into Whole-grain Health Benefitsmentioning
confidence: 98%
“…In the presence of adequate supplies of betaine, less choline is used for the remethylation of homocysteine, allowing choline to be used for the production of phospholipids that make up a large proportion of cell membranes (31) . Postprandial plasma phospholipid concentrations of two phosphatidylcholines increased in both pigs in human subjects (17) , and although betaine was not measured, a post-prandial rise in betaine following eating whole grains has been measured in human subjects (26) . Whole-grain intake was associated with lower fasting plasma phosphatidylcholine concentrations in the European Prospective Investigation into Cancer and Nutrition cohort (32) , although postprandial and fasting samples reflect very different metabolic states.…”
Section: Betaine and Phospholipidsmentioning
confidence: 99%
See 1 more Smart Citation